Reduction of senescent fibro‐adipogenic progenitors in progeria‐aged muscle by senolytics rescues the function of muscle stem cells. Issue 6 (11th October 2022) - Liu, Lei; Yue, Xianlin; Sun, Zewei; Hambright, William S.; Wei, Jianming; Li, Ying; Matre, Polina; Cui, Yan; Wang, Zhihui; Rodney, George; Huard, Johnny; Robbins, Paul D.; et al.
Abstract: Background: Fibro‐adipogenic progenitors (FAPs) in the muscles have been found to interact closely with muscle progenitor/stem cells (MPCs) and facilitate muscle regeneration at normal conditions. However, it is not clear how FAPs may interact with MPCs in aged muscles. Senolytics have been demonstrated to selectively eliminate senescent cells and generate therapeutic benefits on ageing and multiple age‐related disease models. Methods: By studying the muscles and primary cells of age matched WT mice and Zmpste24 −/− (Z24 −/− ) mice, an accelerated ageing model for Hutchinson–Gilford progeria syndrome (HGPS), we examined the interaction between FAPs and MPCs in progeria‐aged muscle, and the potential effect of senolytic drug fisetin in removing senescent FAPs and improving the function of MPCs. Results: We observed that, compared with muscles of WT mice, muscles of Z24 −/− mice contained a significantly increased number of FAPs (2.4‐fold; n > =6, P < 0.05) and decreased number of MPCs (2.8‐fold; n > =6, P < 0.05). FAPs isolated from Z24 −/− muscle contained about 44% SA‐β‐gal+ senescent cells, in contrast to about 3.5% senescent cells in FAPs isolated from WT muscle ( n > =6, P < 0.001). The co‐culture of Z24 −/− FAPs with WT MPCs resulted in impaired proliferation and myogenesis potential of WT MPCs, with the number of BrdU positive proliferative cells being reduced for 3.3 times ( n > =6, P < 0.001) and the number of myosin heavy chain (MHC)‐positive myotubes being reduced for 4.5 times ( n > =6, P < 0.001). The treatment of the in vitro co‐culture system of Z24 −/− FAPs and WT MPCs with the senolytic drug fisetin led to increased apoptosis of Z24 −/− FAPs (14.5‐fold; n > =6, P < 0.001) and rescued the impaired function of MPCs by increasing the number of MHC‐positive myotubes for 3.1 times ( n > =6, P < 0.001). Treatment of Z24 −/− mice with fisetin in vivo was effective in reducing the number of senescent FAPs (2.2‐fold, n > =6, P < 0.05) and restoring the number of muscle stem cells (2.6‐fold, n > =6, P < 0.05), leading to improved muscle pathology in Z24 −/− mice. Conclusions: These results indicate that the application of senolytics in the progeria‐aged muscles can be an efficient strategy to remove senescent cells, including senescent FAPs, which results in improved function of muscle progenitor/stem cells. The senescent FAPs can be a potential novel target for therapeutic treatment of progeria ageing related muscle diseases.